The body in question: metaphor and meaning in the interpretation of Ephesians 5:21-33 - Dawes, Gregory W. (Biblical interpretation series, 1998)
This study is an analysis of the argumentation of Ephesians 5:21-33. The interpretation of this passage remains fiercely contested: while some interpreters appeal to this text to suggest that husbands have authority over their wives, others reject its apparently patriarchal ethic. Approaching Ephesians 5:21-33 by way of a discussion of metaphorical language, the present work shows that its argumentation rests upon two very different uses of the 'body' metaphor. One use highlights the unity of wife and husband, while the other underlines the distinction between the partners and suggests that the husband has a position of authority. The tension created by these two uses of the 'body' metaphor implies that neither a simple hierarchical nor a simple egalitarian interpretation of the passage can be justified.